ANALISIS PRATEK “MANDULANG AMEH” DALAM MENINGKATKAN PENDAPATAN MASYRAKAT (STUDI KASUS: JORONG SILUKAH NAGARI DURIAN GADANG KECAMATAN SIJUNJUNG) - Ranti Oktavia; Zuwardi (Jurnal Ekonomi dan Bisnis, 2023)
This thesis entitled “ Analysis of mandulang Ameh practices in increasing people’s income (case study : Jorong Silukah Nagari Durian Kecamatan Sijunjung)” was written by Ranti Oktavia Nim 3219138 islamic economics study program, faculty of islamic economics and business (FEBI), State Islamic University (UIN) Sjech M. Djamil Djambek Bukittinggi, For guidance from Mr. Zuwardi,MA. The background of the author discusses this title because the practice of ameh mandulang initially used a simple tool called ginger but with the decline in the economic sector the community took the pitas road using boat mines or ameh mandulang using rafts, so the practice of ameh mandulang can open jobs and increase the community's economy. Before the mandulang amch practice, the community's income from farming was not much but with the mandulang ameh income which is currently increasing if there are no constraints from the weather or other things. This research is a field research by collecting data and research locations. The approach in this research is descriptive qualitative research by describing field events according to the data, presenting data and analyzing data and describing existing problem solvers. This method is used to describe something as it is. The results of the study show that the existence of mandulang amch really helps the community to meet the necessities of life and an economy that is already relatively prosperous. We can see this and the practice of ameh mandulang can open up employment opportunities for the community such as rice stalls, mechanics and small stalls that sell the needs of the amch mandulang workers. From the practice of Ameh's mandulang, we can see that primary needs can be met in the form of groceries and others. There are also widespread needs that can be met by Mandulang Ameh workers who own motorized vehicles and even cars at high prices.